Manifestasi Klinis dan Komplikasi Infeksi Dengue pada Anak-Anak: Wawasan dan Perbandingan dengan Kasus pada Dewasa: Tinjauan Pustaka - Kusuma, Sonia Sudana (Cermin Dunia Kedokteran, 2025)
Dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS) have become significant global health concerns, particularly affecting children more severely than adults. In children, dengue infection is distinct from that in adults due to its higher mortality rate and increased risk of developing dengue hemorrhagic fever or dengue shock syndrome. Clinical manifestations vary by age; children more commonly present with vomiting, rash, and abdominal pain, while adults often experience muscle and joint pain. Symptoms of DHF, a severe type of dengue infection, include abnormal hemostasis, plasma leakage, and protein-losing shock syndrome (dengue shock syndrome/DSS). Dengue infection in children can cause various complications from each organ system. During the critical phase, children are prone to plasma leakage, shock, and bleeding, potentially leading to severe complications such as liver dysfunction, electrolyte imbalance, and organ failure. Proper management and prevention of dengue are required to prevent dengue complications.